Individual variation across PROP and thermal taste phenotypes - Yang, Qian (2015)
PROP taster status (PTS) has long been investigated, but thermal taster status (TTS), where thermal tasters (TTs) perceive a ‘phantom taste’ from temperature stimulation is less well understood.